Pembuatan Sabun Cuci Piring Berbahan Dasar Alami Jeruk Nipis Sebagai Alternatif Produk Ramah Lingkungan - Rasyidan, Faiz; Agus Tri Susilo; Hemalia Putri Johar Manik; Zulfa Aswida Najib; Alodia Ikhsanty; Aurellia Febriana Maharani; Cintya Jane Stefany; Hanifa Masrura; Naila Khalila Akbar; Sunu Aziz Wicaksono (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study aims to produce liquid dishwashing soap by integrating synthetic and natural ingredients, namely Sodium Lauryl Ether Sulfate (SLES), salt, food coloring, ethanol, and lime (Citrus aurantiifolia) as a natural-based cleaning agent. Lime was chosen because it contains citric acid and antibacterial compounds that are effective in removing grease and dirt. The method used in this study was an experiment with three variations of lime concentration (10%, 15%, and 20%) to assess its impact on soap quality. The parameters tested included fat-cleaning ability, foam stability, acidity level (pH), and skin irritation potential. The results showed that the formula with 15% lime content was the most optimal, demonstrating efficiency in cleaning tableware, producing stable foam, and having a pH close to neutral, making it safe for use. No irritation reactions were detected on the skin of the respondents. These findings indicate that the combination of natural and synthetic ingredients can produce an effective, economical, and ecological dishwashing soap. This product has the potential to be developed as a safer option for households and the environment.